THE INFLUENCE OF ARTIFICIAL INTELLIGENCE (AI) ON FINANCIAL REPORTING IN COMPANIES LISTED ON THE JAKARTA ISLAMIC INDEX (JII) - Wulandari, Yusma; Damirah; Rismala (Islamic Financial And Accounting Review, 2024)
Artificial Intelligence is a system that can imitate or even surpass human intelligence in completing certain tasks. AI has driven transformation in various sectors, including financial reporting. This research aims to determine the effect of implementing AI in financial reporting in companies listed on the Jakarta Islamic Index (JII). The data used in this research are in the form of company financial reports at JII, namely balance sheets and profit and loss reports. The method used is Artificial Intelligence with variable levels of efficiency, accuracy and data analysis. This type of research is associative with an associative quantitative approach. The data collection technique is a documentation technique. The data analysis technique used is statistical analysis. This research processing uses a formula for efficiency level, accuracy level, data analysis level, and applicationE-views version 12 (X64). With 5 companies that have published financial report data for 3 consecutive years. The research results obtained show 1) The level of efficiency does not have a significant influence onFinancial Reporting, this is proven from the t-test carried out, where it is obtained equal to0.8439 > 0.05, then it can be concluded that H1 is rejected. 2) The level of accuracy has a significant influence on Financial Reporting. This is proven by the t-test carried out, where a value of 0.0089 <0.05 is obtained, so it can be concluded that H2 is accepted. 3) The level of data analysis has a significant influence on Financial Reporting. This is proven by the t-test carried out, where a value of 0.0011 < 0.05 is obtained, so it can be concluded that H3 is accepted.